Scanningless and continuous 3D bioprinting of human tissues with decellularized extracellular matrix. (February 2019) - Yu, Claire; Ma, Xuanyi; Zhu, Wei; Wang, Pengrui; Miller, Kathleen L.; Stupin, Jacob; Koroleva-Maharajh, Anna; Hairabedian, Alexandria; Chen, Shaochen
Abstract: Decellularized extracellular matrices (dECMs) have demonstrated excellent utility as bioscaffolds in recapitulating the complex biochemical microenvironment, however, their use as bioinks in 3D bioprinting to generate functional biomimetic tissues has been limited by their printability and lack of tunable physical properties. Here, we describe a method to produce photocrosslinkable tissue-specific dECM bioinks for fabricating patient-specific tissues with high control over complex microarchitecture and mechanical properties using a digital light processing (DLP)-based scanningless and continuous 3D bioprinter. We demonstrated that tissue-matched dECM bioinks provided a conducive environment for maintaining high viability and maturation of human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes and hepatocytes. Microscale patterning also guided spontaneous cellular reorganization into predesigned striated heart and lobular liver structures through biophysical cues. Our methodology enables a light-based approach to rapidly bioprint dECM bioinks with accurate tissue-scale design to engineer physiologically-relevant functional human tissues for applications in biology, regenerative medicine, and diagnostics. Graphical abstract: